Sex and Gender Differences in Prevention of Type 2 Diabetes - Harreiter, Jürgen; Kautzky-Willer, Alexandra (Frontiers in Endocrinology, 2018)
Lifestyle intervention programs are effective in the prevention of type 2 diabetes mellitus (T2DM) in high risk populations. However, most studies only give limited information about the influence of sex and/or gender effectiveness of these interventions. So far, similar outcome was reported for diabetes progression and weight loss. Nevertheless, long term data on cardiovascular outcome is sparse but favouring women regarding all-cause and cardiovascular mortality. In both men and women, sex hormone imbalances and reproductive disorders are associated with a higher risk of T2DM development. Diabetes prevention approaches are reported for PCOS (polycystic ovary syndrome), GDM (gestational diabetes mellitus) and erectile dysfunction and are presented in this review. In the surgical treatment options for morbid obese patients, sex and gender differences are present. Choices and preferences of adherence to lifestyle and pharmacological interventions, expectations, treatment effects and complications are influenced by sex or gender. In general, bariatric surgery is performed more often in women seeking medical/surgical help to lose weight. Men are older and have higher comorbidities and mortality rates and worse follow up outcome after bariatric surgery. A more gender-sensitive clinical approach, as well as consideration of ethnicity may improve quality of life and increase health and life expectancy in men and women with a high risk for subsequent progression to T2DM.